SKRINING FITOKIMIA DAN ANALISIS KADAR FLAVONOID TOTAL FRAKSI ETIL ASETAT KULIT BUAH DURIAN MERAH (Durio graveolens Becc.) Dengan METODE SPEKTROFOTOMETRI Uv-VIS : SKRINING FITOKIMIA DAN ANALISIS KADAR FLAVONOID TOTAL FRAKSI ETIL ASETAT KULIT BUAH DURIAN MERAH (Durio graveolens Becc.) Dengan METODE SPEKTROFOTOMETRI Uv-VIS - Tri Esti Kusuma Bakti; Mahfur Mahfur (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2023)
Flavonoids are natural compounds found in durian. One of the most important components known as natural compounds, which have the potential as anti-inflammatory and antioxidant. The secondary metabolites of flavonoids in the skin of plants can be affected by the process of photosynthesis. The purpose of this study was to measure the total flavonoid content and ethyl acetate fraction of red durian skin using the Uv-Vis spectrophotometry method. This research uses a type of descriptive research method. Extraction of red durian fruit skin (Durio graveolens Becc) using maceration method with 70% ethanol solvent. Fractionation was carried out using the liquid-liquid fractionation method using ethyl acetate. Thin Layer Chromatography (TLC) was used to identify flavonoids with the stationary phase of silica gel GF254 and the mobile phase of methanol:ethyl acetate 7:3 for flavonoid compounds. Quantitative analysis was carried out using the UV-Vis Spectrophotometry method, to determine the total flavonoid content. The results showed that the ethyl acetate fraction sample was positive for containing alkoloid compounds, flavonoids and did not contain saponins and tannins. The results of the assistance for spots on the TLC plate obtained an Rf value of 0.75-0.81.Â the total flavonoid test results using the Uv-Vis spectrophotometry method of the ethyl acetate fraction of the red durian rind sample yielded a total flavonoid content of 5.706 mg QE/g.